Success of Current COVID-19 Vaccine Strategies vs. the Epitope Topology of SARS-CoV-2 Spike Protein-Receptor Binding Domain (RBD): A Computational Study of RBD Topology to Guide Future Vaccine Design - Santhinissi Addala; Madhuri Vissapragada; Madhumita Aggunna; Niharikha Mukala; Manisha Lanka; Shyamkumar Gampa; Manikanta Sodasani; Jahnavi Chintalapati; Akhila Kamidi; Ravindra P. Veeranna; Ravikiran S. Yedidi (Vaccines, 2022)
Coronavirus disease-2019 (COVID-19) is a pandemic with a high morbidity rate occurring over recent years. COVID-19 is caused by the severe acute respiratory syndrome causing coronavirus type-2 (SARS-CoV-2). COVID-19 not only challenged mankind but also gave scope to the evolution of various vaccine design technologies. Although these vaccines protected and saved many lives, with the emerging viral strains, some of the strains may pose a threat to the currently existing vaccine design that is primarily based on the wild type spike protein of SARS-CoV-2. To evaluate the risk involved from such mutant viral strains, we performed a systematic in silico amino acid substitution of critical residues in the receptor binding domain (RBD) of the spike protein. Our molecular modeling analysis revealed significant topological changes in the RBD of spike protein suggesting that they could potentially contribute to the loss of antigen specificity for the currently existing therapeutic antibodies/vaccines, thus posing a challenge to the current vaccine strategies that are based on wild type viral spike protein epitopes. The structural deviations discussed in this article should be considered carefully in the future vaccine design.